Sclerosing mucoepidermoid carcinoma with eosinophilia of the salivary gland: Case report and review of the literature. (22nd February 2013) - Tasaki, Takashi; Matsuyama, Atsuji; Tabata, Takahisa; Suzuki, Hideaki; Yamada, Sohsuke; Sasaguri, Yasuyuki; Hisaoka, Masanori
<x xml:space="preserve">Abstract</x> Sclerosing mucoepidermoid carcinoma with eosinophilia (SMCE) of the salivary gland is a rare variant of mucoepidermoid carcinoma. We report a case of SMCE in the right submandibular gland of a 79‐year‐old man. Fine needle aspiration cytology revealed cohesive clusters of atypical squamous epithelial cells admixed with cells containing intracytoplasmic mucin and eosinophils. Histologically, the tumor was composed of epithelial nests with keratinizing cells occasionally present at the center, as well as peripherally located atypical basaloid cells, and some mucin‐containing cells embedded in a fibrosclerotic stroma, which were accompanied by a prominent lymphoplasmacytic and eosinophilic infiltrate. Inflammatory infiltrate and stromal fibrosclerosis also were seen in the non‐neoplastic salivary gland tissue adjacent to the tumor. Immunohistochemically, many plasma cells were IgG4‐positive. The postoperative serum IgG4 level was elevated. Our reverse transcription‐polymerase chain reaction using formalin‐fixed, paraffin‐embedded tumor tissue failed to detect any fusion‐gene transcripts which are specifically identified in ordinary mucoepidermoid carcinoma. The findings of the present case suggest that this rare type of salivary gland carcinoma may be associated with a chronic inflammatory condition such as IgG4‐related sclerosing disease. Only 23 cases of sclerosing mucoepidermoid carcinoma with or without eosinophilic infiltratie have been reported to date in such an anatomical location.